The impact on the mental health of healthcare professionals in front of the COVID-19 (Research, Society and Development, 2021)
In a pandemic scenario due to the emergence of a new virus, a notable expectation has been generated around the performance of healthcare professionals as one of the essential pillars in the fight against COVID-19. However, the mental health of these professionals, who practice their profession under high levels of pressure and stress has been damage. To analyze the impact on mental health of healthcare professionals who work on the front line in the fight against COVID-19. It is characterized by a cross-sectional study of quali-quantitative approach, which aimed to analyze the mental health of 100 individuals who were active in the health service of the city of Lages - SC, applying a questionnaire prepared by the authors themselves. It was evident that 86% (n = 86) of the interviewees had already had previous contact with a patient suspected or confirmed with COVID-19 in the work environment and more than half of the professionals had feelings like anxiety, nervousness, tension and difficulty to relax outside the professional field. It has been shown that healthcare workers, especially those in contact with patients infected or suspected by COVID-19 had an impact on mental health during the pandemic. Therefore, it is necessary to develop new studies to identify in more detail the psychological overload on these professionals, in addition to fostering strategies aimed at promoting their mental health.